Modified atmosphere storage of minimally processed Cantaloupe (Cucumis melo L. var. Reticulatus cv. Glamour) - Kamaruddin, Syahidah; Shamsudin, Rosnah; Mohd Adzahan, Noranizan; Othman, Zaulia; Ahmedov, Anvarjon (Canadian Center of Science and Education, 2014)
Cantaloupe (Cucumis melo L. var. Glamour) is a type of melon which is characterised by its netted surface. This study was conducted to determine the effects of different sealed packaging materials on the changes in quality of fresh-cut Cantaloupe during storage at 2 °C and 87% RH for 18 days. The selection of packaging materials is critical to the development of a modified environment inside the package. The fresh-Cut Cantaloupe fruits (Cucumis melo L. var. Glamour) were packed in Polypropylene (PP) containers and sealed with 40 µm Low-Density Polyethylene (LDPE) films and Polypropylene (PP) films. For the control sample, a Polypropylene (PP) container was closed using a lid cover (PP) without a sealing film. Sample 1 (S1) consisted of a Polypropylene (PP) container sealed only with a 40 µm PP film and Sample 2 (S2) comprised of a Polypropylene (PP) container sealed with a 40 µm LDPE film. The samples were analysed after storage at 2 °C for 18 days. The Cantaloupe fruits were cut into small cubes of 2 cm × 2 cm × 2 cm. Evaluation parameters include colour, firmness, respiration rate, Total Plate Count (TPC) and Yeast and Mould (YM). Overall for both packages the results indicated that the respiration rate, firmness, Total Plate Count (TPC) and Yeast and Mould (YM) decreased significantly (p < 0.05), while colour (luminosity, hue angle and chromaticity) were not significantly (p > 0.05) different. Samples from the packages sealed with LDPE (S2) indicated better appearance and quality.Thus, LDPE is recommended to be used for packaging of fresh-cut Cantaloupe.